Mapping of seagrass ecosystem on Bontosua Island, Pangkep District, South Sulawesi, Indonesia - DWI ROSALINA; KHAIRUL JAMIL; YASSER ARAFAT; REZKI AMALIA; ANI LEILANI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Rosalina D, Jamil K, Arafat Y, Amalia R, Leilani A. 2023. Mapping of seagrass ecosystem on Bontosua Island, Pangkep District, South Sulawesi, Indonesia. Biodiversitas 24: 2023-2030. Bontosua Island is one of the islands in South Sulawesi, Indonesia, that has a seagrass ecosystem. The purpose of this study was to assess the density, cover, area, and condition of seagrass on Bontosua Island. The data collection involved the use of a quadratic transect method in the field and the Lyzenga method for remote sensing. The identification of seagrass areas was made using Landsat 8 OLI/TIRS satellite. Six seagrass species were identified, namely Cymodocea rotundata, Thalassia hemprichii, Halodule uninervis, Halodule pinifolia, Syringodium isoetifolium and Halophila sp. The results showed that C. rotundata had the highest density value of 89 Ind/m² and was categorized as rather dense, while C. rotundata also had the highest percentage cover of 58%, and Halophila sp. had the lowest percentage cover of 2%. The distribution area of seagrass beds on Bontosua Island was approximately 28.26 ha, out of a total area of 92 ha, of which approximately 6 ha was land. Observations on the condition of seagrass beds showed that 16.65 ha was healthy, 6.3 ha was unhealthy, while 5.31 ha was poor.